АНАЛИЗ СОРЕВНОВАТЕЛЬНОЙ ДЕЯТЕЛЬНОСТИ ВЫСОКОКВАЛИФИЦИРОВАННЫХ КУРАШИСТОВ - Нурышов, Д. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of analytical elements of technical-tactic abilities of fighters. There have been distinguished such parameters as stability, ability to master the technical-tactic techniques of a competitor, the structure and others.